PRIVILEGES AND IMMUNITIES OF THE SHANGHAI COOPERATION ORGANISATION AS ELEMENTS OF HER INTERNATIONAL RIGHT SUBJECTIVITY (International relations and international law Journal, 2016)
The article considers the privileges and immunities of Shanghai Сooperation Organization in the context of determining the legal status of the SCO as a subject of international law. There given an analysis of articles of the 2004 Convention on the Privileges and Immunities of the SCO.
Keywords: privileges; immunities; SCO